Trends in Māori wellbeing: Background paper to Te Tai Waiora: Wellbeing in Aotearoa New Zealand 2022 - Chelsey Reid; Phil Evans (New Zealand Government, The Treasury, 2022)
This paper provides an exploration of current and emerging trends in Māori wellbeing using He Ara Waiora. The paper draws on quantitative evidence, including indicators from the LSF Dashboard and Indicators Aotearoa New Zealand. The analysis is also supported by qualitative evidence in the form of interview quotes from Māori participants and associated commentary.
Keywords: 330; Maori; Soziale Lage; Lebensqualität; Sozialer Indikator; Neuseeland